Label-free methods for studying protein-protein interactions - Valtonen, Salla (fi=Turun yliopisto|en=University of Turku|, 2021)
Proteins are the building blocks of life, and mainly perform their roles through protein-protein interactions (PPIs). Thus, PPIs are essential to the normal function of the cells and the body, and disturbances in these interactions are an underlying cause for many diseases. Because PPIs are so vital, multiple methods have been developed to study these interactions. Typically, the methods are based on reporter molecules, although label conjugation may disrupt PPIs. Several label-free methods have also been introduced, which can be categorized into surface-based and solutionbased approaches. Surface-based methods are often very sensitive, but they require protein conjugation to a solid surface. Solution-based methods, on the other hand, are fully conjugation-free but suffer from low sensitivity. In this thesis, a label-free, solution-based Protein-Probe method with nanomolar sensitivity was developed for studying protein thermal stability and interactions. The method is based on an external probe peptide, the Eu-probe, and it does not require conjugation to the interacting proteins, avoiding potential disruption of the reactions. The Eu-probe does not significantly bind to native, intact proteins, and the timeresolved luminescence signal of the free probe is quenched by a modulator in the Protein-Probe solution. When denaturation reveals hydrophobic amino acids or binding events increase the overall surface area, the change in the protein structure enables the Eu-probe binding. Binding to the proteins protects the probe from the modulator and leads to a signal increase. The Protein-Probe was first applied to studying protein-ligand interactions and PPIs by observing their effect on protein thermal stability in thermal shift assays. PPIs were also monitored based on interaction-induced signal increase at elevated temperatures without a thermal shift, and in competitive thermal shift assays with small molecular ligands. The formation of large protein complexes and aggregates was successfully monitored at room temperature. The developed label-free Protein- Probe method has improved sensitivity over the current solution-based PPI detection techniques. The method enables monitoring different interaction types, as the external probe binds to a wide variety of proteins in multiple assay concepts. Thus, the Protein-Probe is a promising new method for PPI studies.

Leimavapaat menetelmät proteiinien välisten vuorovaikutusten tutkimiseen Proteiinit ovat yksi elämän rakennuspalikoista, ja ne toimivat pääasiassa proteiinien välisten vuorovaikutusten (PPI:t) kautta. Tämän vuoksi PPI:t ovat elintärkeitä solujen ja kehon normaalille toiminnalle, ja häiriöt vuorovaikututuksissa ovat usean sairauden takana. Koska PPI:t ovat niin keskeisiä, niiden tutkimiseen on kehitetty useita menetelmiä. Tyypillisesti menetelmät perustuvat reportterimolekyyleihin, vaikka niiden kiinnitys saattaa häiritä PPI:tä. On olemassa myös useita leimavapaita menetelmiä, jotka voidaan jakaa pintapohjaisiin ja liuospohjaisiin menetelmiin. Pintapohjaisilla menetelmillä on usein hyvä herkkyys, mutta niiden heikkous on että proteiini täytyy konjugoida kiinteään pintaan. Liuospohjaiset menetelmät taas eivät vaadi ollenkaan konjugaatiota, mutta kärsivät usein huonosta herkkyydestä. Tässä työssä kehitettiin leimavapaa, liuospohjainen ”Protein-Probe” menetelmä, jonka herkkyys on nanomolaarisella alueella. Menetelmä perustuu ulkoiseen koetinpeptidiin, Eu-koettimeen, joten tutkittavia proteiineja ei konjugoida. Eu-koetin ei sitoudu merkittävästi natiivirakenteisiin proteiineihin, ja Protein-Probe-liuoksessa oleva modulaattori sammuttaa vapaan koettimen aikaerotteisen luminesenssisignaalin. Muutokset proteiinien rakenteessa, kuten denaturaatiosta johtuva hydrofobisten aminohappojen paljastuminen ja vuorovaikutuksia seuraava pintaalan kasvu, mahdollistavat Eu-koettimen sitoutumisen. Sitoutuminen proteiineihin suojaa koetinta modulaattorilta ja johtaa näin signaalin kasvuun. Protein-Probe-menetelmällä tutkittiin proteiini-ligandi- ja proteiini-proteiinivuorovaikutuksia seuraamalla niiden vaikutusta proteiinien lämpöstabiilisuuteen ”thermal shift” määrityksissä. Vuorovaikutuksia havainnoitiin myös perustuen sitoutumisen aikaansaamaan signaalin nousuun korkeassa lämpötilassa, ja kilpailevissa thermal shift määrityksissä pienten ligandimolekyylien kanssa. Suurten proteiinikompleksien ja aggregaattien muodostuminen havaittiin huoneenlämmössä. Kehitetty leimavapaa Protein-Probe menetelmä on herkempi kuin nykyiset liuospohjaiset tekniikat, ja sillä on mahdollista tutkia erilaisia vuorovaikutuksia, koska ulkoinen koetin sitoutuu moneen eri proteiiniin useassa määritystyypissä. Protein-Probe-menetelmä on siis lupaava uusi menetelmä PPI-tutkimukseen.